Production and characterization of microsphere reinforced polyester composite: Modeling of thermal decomposition with ANN and optimization studies by RSM - Aydogmus, Ercan; Aydin, Muhammet; Arslanoglu, Hasan (Taylor & Francis Inc, 2024)
In this research, hollow inorganic microsphere (Q-cel) reinforced unsaturated polyester composite is produced, and its thermophysical properties have been characterized. The thermal decomposition kinetics of the composite obtained at different heating rates and various compositions are modeled using artificial neural networks. Also, the production optimization of the polyester composite has been evaluated using response surface methodology. The study has been repeated for certain heating rates (5, 10, and 20 K/min). Activation energies of polyester composites have been calculated using thermogravimetric data and kinetic methods. Changes in activation energy during the thermal decomposition (4 wt.% Q-cel, 94 wt.% UP, 580-660 K, and 20 K/min) of the composite are compared using FWO (129.4 kJ/mol), KAS (127.6 kJ/mol), and CR (126.5 kJ/mol). According to the results, it is seen that the activation energy goes up as the temperature and Q-cel ratio by the mass increase. When the amount of the filler in the polyester composite increases, the thermal conductivity coefficient also rises. As well as, it is determined that as Q-cel ratio in the mixture raises, the density of the composite decreases and Shore D hardness goes up.
Keywords: composite; density; hardness; hollow inorganic microsphere; thermal conductivity; thermal decomposition